2020
DOI: 10.2478/raft-2020-0028
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Talent Management Intricacies of Remote Cybersecurity Teams in Covid-19 Induced Telework Organizational Ecosystems

Abstract: The unanticipated disruption triggered by Coronavirus, also known as COVID-19, has accelerated the shift to virtual workplace ecosystems for employees in the government, business, and the military. The accelerated move to whole organization telework has also created new complex challenges around managing cybersecurity risks. Complex business and governmental organizational ecosystems have several significant and critical job tasks around cybersecurity. These roles have the involved responsibility of functionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 5 publications
(13 reference statements)
0
59
0
Order By: Relevance
“…The COVID-19 pandemic has resulted in substantial changes in childcare circumstances and employment and working conditions, with a considerable shift toward tele-work ( Figure 1) [30]. In this study, 45.6% of household food purchasers reported that at least one adult in their household substituted all of their in-person work with telework, 26.9% reported that at least one adult substituted some of their in-person work with telework, and 27.5% reported that no adults in their household substituted their in-person work with telework.…”
Section: Covid-19-related Household Changesmentioning
confidence: 99%
“…The COVID-19 pandemic has resulted in substantial changes in childcare circumstances and employment and working conditions, with a considerable shift toward tele-work ( Figure 1) [30]. In this study, 45.6% of household food purchasers reported that at least one adult in their household substituted all of their in-person work with telework, 26.9% reported that at least one adult substituted some of their in-person work with telework, and 27.5% reported that no adults in their household substituted their in-person work with telework.…”
Section: Covid-19-related Household Changesmentioning
confidence: 99%
“…] in organizations where teleworking is officially allowed, it is seldom used as a standard strategy but more as a form of crisis management in order to be able to cope [. COVID-19 caused organizations that previously chided teleworking to react and hastily strategize, migrate and adapt to teleworking (Burrell, 2020). In comparison, organizations that already had telecommuting policies, along with the infrastructure and technology in place for teleworking, were better positioned to respond to the telework mandate (Burrell, 2020).…”
Section: Impact Of Covid-19 On Organizationsmentioning
confidence: 99%
“…COVID-19 caused organizations that previously chided teleworking to react and hastily strategize, migrate and adapt to teleworking (Burrell, 2020). In comparison, organizations that already had telecommuting policies, along with the infrastructure and technology in place for teleworking, were better positioned to respond to the telework mandate (Burrell, 2020). However, the underlying commonality is that COVID-19 globally challenged every industry and organization with unprecedented hardships.…”
Section: Impact Of Covid-19 On Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizations living on the edge of chaos and change are invested in changing behavior and require a new pattern of interaction (Cheung-Judge & Holbeche, 2015;Burrell, 2020). The concepts of changing behavior by changing language and leveraging group dynamics to shift behavior offer an alternative for changing behaviors in organizations (Cheung-Judge & Holbeche, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%